Optimal extent of lymph node dissection in gastric cancer - Varga, Zsolt; Kolozsi, Péter; Nagy, Kitti; Tóth, Dezső (Frontiers in Surgery, 2022)
Gastric cancer still remains a major cause of cancer-related deaths globally. Stage-adapted, individualized treatment is crucial to achieving optimal oncological outcomes. Postoperative morbidity and accurate nodal staging are heavily influenced by the extent of lymph node dissection. On one hand, insufficient lymphadenectomy may result in understaging and undertreatment of a patient, on the other hand, unnecessary lymph node dissection may result in a higher rate of postoperative complications. Approximately one-third of patients with gastric cancer undergo an avoidable lymph node dissection. Many of the recent treatment updates in the management of gastric cancer have a major influence on both surgical and oncological approaches. Currently, a wide range of endoscopic, minimally invasive, and hybrid surgical techniques are available. The concept of sentinel node biopsy and utilization of the Maruyama Computer Program are significant components of stage-adapted gastric cancer surgery. Likewise, centralization and application of national guidelines, widespread use of neoadjuvant therapy, and the stage migration phenomenon are serious concerns to be discussed. Our goal is to review the available surgical strategies for gastric cancer, with a primary focus on lymphadenectomy.